Biological treatment in elderly and young patients with ankylosing spondylitis: TURKBIO real-life data results - Ayşe Cefle; Fatoş Önen; Nurullah Akkoç; Merih Birlik; İsmail Sarı and Özgül Soysal Gündüz and Sema Yılmaz and Servet Yolbaş and Aydan Köken Avşar and Sadettin Uslu and et al. (Archives of Rheumatology, 2024)
Objectives: This study aims to investigate the effect of age on disease activity and biological treatment in patients with ankylosing spondylitis (AS). Patients and methods: A total of 811 AS patients registered in the TURKBIO registry database between 2011 and 2019 were categorized according to their age at the time of entry into the registry and assigned to one of two groups: young patients, defined as <60 years of age (n=610), and those aged ≥60 years (n=201) were recorded as elderly patients. Demographic, clinical, and laboratory characteristics, along with disease activity markers and other follow-up parameters, as well as current and prior treatments, were electronically recorded during each visit using open-source software. Results: The mean age of the elderly patients was 67±5.8 years, while the mean age of the younger patients was 49.2±10.9 years. Male predominance was lower in the older AS group compared to the younger AS group (p=0.002). During follow-up period, 397 patients (comprising 318 young and 79 elderly individuals) had a history of using at least one biological disease-modifying agent (bDMARD). There was no significant difference between the groups in terms of DMARD and bDMARD-use distributions. First tumor necrosis factor inhibitor (TNFi) retention rates were found to be similar in both groups over 10 years of follow-up. Adverse events were found to be similar in young (19.9%) and elderly (26.8%) AS patients. Conclusion: Research in the TURKBIO cohort reveals that both older and younger patients with AS exhibited similar disease activity levels with comparable treatment approaches. Moreover, the results of TNFi treatments in elderly patients were the same as those observed in younger patients, with no notable increase in safety concerns.